Cr / CrN / WC / C nano coating as well as preparation method and application thereof
By using a Cr/CrN/WC/C nano-coating structure and high-power magnetron sputtering technology, the problem of insufficient strength and toughness of the coating for small-hole boring tools was solved, resulting in a coating with high strength and excellent adhesion, which improves the cutting performance and service life of the boring tool.
Patent Information
- Application Number
- CN202411405481.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Existing small hole boring tool coatings suffer from insufficient toughness, poor adhesion, and uneven coating during use, failing to meet processing requirements.
The Cr/CrN/WC/C nano-coating structure consists of a Cr metal bonding layer, a CrN nanocomposite coating, a WC nano-coating, and a C coating, arranged from bottom to top. It is prepared by high-power magnetron sputtering technology, and the thickness and deposition conditions of each layer are controlled to improve the bonding strength and toughness.
It significantly improves the cutting performance and lifespan of small hole boring tools. The coating has high strength and toughness, excellent adhesion and oxidation resistance, making it suitable for mass production.
Smart Images

Figure CN119287325A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fine machining, and in particular to a Cr / CrN / WC / C nano coating and a preparation method and application thereof. Background Art
[0002] Boring cutters are a type of boring tool, usually with round handles. The most common occasions are internal hole processing, hole expansion, profiling, etc.; they have one or two cutting parts and are tools specifically used for rough processing, semi-finishing or finishing of existing holes. Boring cutters are indispensable tools for finishing small and medium holes. The tip of the small hole boring cutter has a sharp blade, which is easy to break during use, thus affecting the workpiece and increasing the processing cost. In order to solve such problems, two main methods are used. One is to study alloys with higher strength, but the research and development is difficult, the technical requirements are high, and the cycle is long; the other is to prepare a coating on the surface of the small hole boring cutter to improve the strength of the tip. Although the technical requirements for the preparation of the coating are low, the current coating preparation technology mostly uses multi-arc ion plating, magnetron and other technologies. The prepared coating still has the disadvantages of insufficient toughness, poor bonding between the coating and the substrate, and uneven coating, which cannot meet the processing requirements. Therefore, providing a new coating that can be used for small hole boring cutters has become an urgent problem to be solved. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the prior art and provide a Cr / CrN / WC / C nano coating and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a Cr / CrN / WC / C nano coating, which comprises, from bottom to top, a Cr metal bonding layer, a CrN nano composite coating, a WC nano coating and a C coating;
[0006] The thickness of the Cr metal bonding layer is 200-500nm; the thickness of the CrN nano-composite coating is 300-500nm; and the thickness of the WC nano-coating is 600-1500nm.
[0007] The present invention also provides a method for preparing the Cr / CrN / WC / C nano coating, comprising the following steps:
[0008] (1) Using Cr target material to activate and pulse magnetron sputter the substrate to form a Cr metal bonding layer;
[0009] (2) using a Cr target to perform pulsed magnetron sputtering on the surface of the Cr metal bonding layer to form a CrN nanocomposite coating;
[0010] (3) pulsed magnetron sputtering is performed on the surface of the CrN nanocomposite coating using a WC target and a C target to form a WC nanocoating;
[0011] (4) Using a C target material to perform pulsed magnetron sputtering on the surface of the WC nano coating to form a C coating, thereby obtaining the Cr / CrN / WC / C nano coating.
[0012] Preferably, the activation micropulse parameters in step (1) are 2 to 40 μs, the average power is 2 to 10 kW, the gas pressure is 0.3 to 2 Pa, the argon gas flow rate is 100 to 130 sccm, and the bias voltage is -30 to -200 V.
[0013] Preferably, the bias voltage of the pulsed magnetron sputtering in step (1) is -60 to -100V.
[0014] Preferably, the micropulse parameters of the pulse magnetron sputtering in step (2) are 2 to 40 μs, the average power is 2 to 10 kW, the gas pressure is 0.8 to 2 Pa, the argon flow rate is 100 to 130 sccm, the nitrogen flow rate is 30 to 120 sccm, and the bias voltage is -60 to -150 V.
[0015] Preferably, in step (3), the micro-pulse parameters of the pulsed magnetron sputtering of the WC target are 6 to 30 μs, and the average power is 6 to 10 kW;
[0016] The pulsed DC power supply parameters for pulsed magnetron sputtering of the C target material in step (3) are 80 to 120 kHz, and the average power is 0.4 to 8 kW.
[0017] Preferably, the gas pressure of the pulse magnetron sputtering in step (3) is 0.6 to 2 Pa, the argon flow rate is 100 to 130 sccm, the nitrogen flow rate is 100 to 130 sccm, and the bias voltage is -60 to -300 V.
[0018] Preferably, the micro-pulse parameters of the pulse magnetron sputtering in step (4) are 2 to 40 μs, the average power is 2 to 10 kW, the gas pressure is 0.8 to 2 Pa, the argon gas flow rate is 100 to 130 sccm, the bias voltage is -60 to -150 V, and the time is 30 to 60 min.
[0019] The invention also provides application of the Cr / CrN / WC / C nano coating in a small hole boring tool.
[0020] The present invention provides a Cr / CrN / WC / C nano coating, which is a high-strength and tough hydrogen-free carbon-based nano coating. Among them, the bonding layer is a metal Cr layer. The design innovation of this coating lies in the use of temperature-resistant Cr as the bonding layer, and the thickness is controlled at 200-500nm. Under the premise of ensuring excellent bonding performance, a wide temperature range bonding strength design is achieved. In addition, high-power magnetron sputtering Cr target, regulating the ion bombardment energy, can achieve ion-enhanced deposition of Cr layer, and significantly improve the bonding strength.
[0021] The present invention uses CrN as a gradient transition layer, with a thickness controlled at 300-500nm, and adopts high-power magnetron sputtering ion-enhanced composite deposition technology to continuously grow dense CrN on the Cr bonding layer, while maintaining a gradient increase in mechanical properties, maintaining continuous and dense growth in structure, and having better anti-oxidation performance than the Cr layer. Therefore, the design and preparation of the CrN layer is a structural gradient and functional gradient coating (mechanical and anti-oxidation performance).
[0022] The WC layer involved in the present invention is a high-strength and toughness layer of the coating, with a thickness controlled at 600-1500nm, which can improve the toughness of the entire coating. The high-power magnetron sputtering ion-enhanced composite deposition technology is used to prepare a dense WC nano coating with a nano hardness of 35-45GPa, H / E* (E* is the effective Young's modulus) greater than 0.1, H 3 / E* 2 ≥0.3, membrane-base bonding strength (Rockwell indentation bonding strength ≥HF1), elastic recovery ≥60%, fracture toughness K IC ≥3MPa·m 1 / 2 .
[0023] The present invention selects the C layer as the lubricating layer to provide mechanical lubrication for the high-strength and toughness nano coating, thereby promoting the friction coefficient to be further reduced to a friction coefficient of ≤0.1 during the mechanical cutting process.
[0024] The present invention also provides a method for preparing the Cr / CrN / WC / C nano coating. The performance of the coating can be accurately controlled by regulating the pulse parameters, deposition conditions, and bias settings of high-power pulsed magnetron sputtering and pulsed DC magnetron sputtering. The method has fast deposition rate, simple operation, low cost, and is suitable for mass production.
[0025] The Cr / CrN / WC / C nano coating provided by the invention is applied to small hole and deep hole boring cutter cutting processing and can significantly improve the cutting performance and service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical picture of the Cr / CrN / WC / C nano coating in Example 1;
[0027] Figure 2This is the indentation test diagram of the Cr / CrN / WC / C nanocoating in Example 1. DETAILED DESCRIPTION
[0028] The invention provides a Cr / CrN / WC / C nano coating, which comprises, from bottom to top, a Cr metal bonding layer, a CrN nano composite coating, a WC nano coating and a C coating.
[0029] In the present invention, the thickness of the Cr metal bonding layer is 200 to 500 nm, preferably 240 to 460 nm, more preferably 280 to 420 nm, and even more preferably 330 to 370 nm.
[0030] In the present invention, the thickness of the CrN nanocomposite coating is 300-500 nm, preferably 330-470 nm, more preferably 360-440 nm, and even more preferably 380-420 nm.
[0031] In the present invention, the thickness of the WC nano coating is 600 to 1500 nm, preferably 700 to 1400 nm, more preferably 800 to 1300 nm, and even more preferably 900 to 1200 nm.
[0032] The present invention also provides a method for preparing the Cr / CrN / WC / C nano coating, comprising the following steps:
[0033] (1) Using Cr target material to activate and pulse magnetron sputter the substrate to form a Cr metal bonding layer;
[0034] (2) using a Cr target to perform pulsed magnetron sputtering on the surface of the Cr metal bonding layer to form a CrN nanocomposite coating;
[0035] (3) pulsed magnetron sputtering is performed on the surface of the CrN nanocomposite coating using a WC target and a C target to form a WC nanocoating;
[0036] (4) Using a C target material to perform pulsed magnetron sputtering on the surface of the WC nano coating to form a C coating, thereby obtaining the Cr / CrN / WC / C nano coating.
[0037] In the present invention, the substrate in step (1) is cleaned before use, the cleaning medium is ethanol or acetone, and the ultrasonic cleaning time is preferably 15 to 20 minutes, more preferably 16 to 19 minutes, and more preferably 17 to 18 minutes.
[0038] In the present invention, the cleaned substrate is placed in a vacuum chamber, and the vacuum degree is preferably ≤1*10 -3 Pa, preferably ≤0.8*10 -3 Pa, preferably ≤0.5*10 -3Pa.
[0039] In the present invention, after the vacuum degree reaches the requirement, the substrate is ion cleaned, and a pulsed DC current is connected to the substrate. The bias voltage of the ion cleaning is preferably -500-600V, more preferably -300-400V, and more preferably -100-200V; the pulsed DC power supply parameters are preferably 80-120KHz, more preferably 85-115KHz, and more preferably 90-110KHz; the pulsed DC power supply parameters are preferably 1-5μs, more preferably 2-4μs, and more preferably 3μs; the gas pressure is preferably 0.3-2Pa, more preferably 0.5-1.5Pa, and more preferably 0.8-1.2Pa; the argon gas flow rate is preferably 100-130sccm, more preferably 105-125sccm, and more preferably 110-120sccm; the time is preferably 30-60min, more preferably 35-55min, and more preferably 40-50min.
[0040] In the present invention, the micropulse parameters of the activation in step (1) are preferably 2 to 40 μs, more preferably 10 to 30 μs, and more preferably 15 to 25 μs; the average power is preferably 2 to 10 kW, more preferably 3 to 9 kW, and more preferably 4 to 8 kW; the gas pressure is preferably 0.3 to 2 Pa, more preferably 0.5 to 1.5 Pa, and more preferably 0.8 to 1.2 Pa; the argon gas flow rate is preferably 100 to 130 sccm, more preferably 105 to 125 sccm, and more preferably 110 to 120 sccm; the bias voltage is preferably -30 to -200 V, more preferably -50 to -180 V, and more preferably -80 to -150 V; the time is preferably 1 to 5 min, more preferably 2 to 4 min, and more preferably 2.5 to 3.5 min.
[0041] In the present invention, the purpose of activation in step (1) is to activate the substrate surface by ion bombardment, improve the ion surface migration ability, and promote nucleation.
[0042] In the present invention, the bias voltage of the pulsed magnetron sputtering in step (1) is preferably -60 to -100 V, more preferably -70 to -90 V, and even more preferably -75 to -80 V.
[0043] In the present invention, the micropulse parameters of the pulse magnetron sputtering in step (2) are preferably 2 to 40 μs, more preferably 5 to 30 μs, and more preferably 10 to 20 μs; the average power is preferably 2 to 10 kW, more preferably 3 to 9 kW, and more preferably 4 to 8 kW; the gas pressure is preferably 0.8 to 2 Pa, more preferably 1 to 1.8 Pa, and more preferably 1.3 to 1.5 Pa; the argon flow rate is preferably 100 to 130 sccm, more preferably 105 to 125 sccm, and more preferably 110 to 120 sccm; the nitrogen flow rate is preferably 30 to 120 sccm, more preferably 40 to 100 sccm, and more preferably 60 to 80 sccm; the bias voltage is preferably -60 to -150 V, more preferably -80 to -140 V, and more preferably -100 to -120 V.
[0044] In the present invention, in step (3), the WC target is connected to a high-power pulse power supply or a deep oscillation power supply to ensure a sufficient ionization rate. The micro-pulse parameters of the pulsed magnetron sputtering using the WC target are preferably 6 to 30 μs, more preferably 10 to 25 μs, and more preferably 15 to 20 μs; the average power is preferably 6 to 10 kW, more preferably 7 to 9 kW, and more preferably 7.5 to 8 kW.
[0045] In the present invention, in step (3), the C target is connected to a pulsed DC power supply, and the pulsed DC power supply parameters for pulsed magnetron sputtering using the C target are preferably 80 to 120 kHz, more preferably 85 to 115 kHz, and more preferably 90 to 110 kHz; the average power is preferably 0.4 to 8 kW, more preferably 2 to 6 kW, and more preferably 3 to 5 kW.
[0046] In the present invention, the gas pressure of the pulse magnetron sputtering in step (3) is preferably 0.6 to 2 Pa, more preferably 1 to 1.5 Pa, and more preferably 1.2 to 1.3 Pa; the argon flow rate is preferably 100 to 130 sccm, more preferably 105 to 125 sccm, and more preferably 110 to 120 sccm; the nitrogen flow rate is preferably 100 to 130 sccm, more preferably 105 to 125 sccm, and more preferably 110 to 120 sccm; the bias voltage is preferably -60 to -300 V, more preferably -80 to -250 V, and more preferably -100 to -200 V.
[0047] In the present invention, the graphite target (C) and the WC target are ionized, and a plasma chemical reaction occurs to recombine into a WC coating. The ionized C (SP3) promotes the combination with the W ions, and at the same time, part of the C exists in the form of graphite (SP2).
[0048] In the present invention, the micropulse parameters of the pulsed magnetron sputtering in step (4) are preferably 2 to 40 μs, more preferably 10 to 30 μs, and more preferably 15 to 25 μs; the average power is preferably 2 to 10 kW, more preferably 4 to 8 kW, and more preferably 5 to 6 kW; the gas pressure is preferably 0.8 to 2 Pa, more preferably 1 to 1.8 Pa, and more preferably 1.2 to 1.5 Pa; the argon gas flow rate is preferably 100 to 130 sccm, more preferably 105 to 125 sccm, and more preferably 110 to 120 sccm; the bias voltage is preferably -60 to -150 V, more preferably -80 to -140 V, and more preferably -100 to -120 V; the time is preferably 30 to 60 min, more preferably 35 to 55 min, and more preferably 40 to 50 min.
[0049] In the present invention, after the pulsed magnetron sputtering in step (4) is completed, the Cr / CrN / WC / C nano coating is obtained by standing still, and the standing time is preferably 30 to 60 minutes, more preferably 35 to 55 minutes, and more preferably 40 to 50 minutes.
[0050] The invention also provides application of the Cr / CrN / WC / C nano coating in a small hole boring tool.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] The substrate was ultrasonically cleaned in ethanol for 15 min, and then blown dry with compressed air. The substrate was placed on the sample platform of the vacuum chamber and the vacuum degree was controlled to 0.8*10 -3 Pa; connect a pulsed DC power supply to the substrate, set the bias voltage to 200V, 100KHz, 1μs, the gas pressure to 1Pa, the argon flow rate to 120sccm, clean for 40min, and complete ion cleaning.
[0054] Connect the Cr target, enable high-power pulsed magnetron sputtering, set the micro-pulse parameters to 25μs, the average power to 8kW, the gas pressure to 1Pa, the argon flow rate to 120sccm, the bias voltage to -80V, and activate for 3min; then change the bias voltage to -60V to prepare a Cr metal bonding layer with a thickness of 300nm.
[0055] High-power pulsed magnetron sputtering was enabled, and the micro-pulse parameters were set to 30 μs, the average power to 5 kW, the gas pressure to 1 Pa, the argon flow rate to 110 sccm, the nitrogen flow rate to 40 sccm, and the bias voltage to -110 V to prepare a CrN nano-composite coating with a thickness of 400 nm.
[0056] The WC target was connected to a high-power pulse power supply, and the C target was connected to a pulsed DC power supply. The micropulse parameters of the pulsed magnetron sputtering of the WC target were 25 μs and the average power was 10 kW. The pulsed DC power supply parameters of the pulsed magnetron sputtering of the C target were 100 kHz, 6 kW, gas pressure 1.5 Pa, argon flow rate 120 sccm, nitrogen flow rate 120 sccm, and bias voltage -240 V to prepare a 1000 nm WC nanocoating.
[0057] Connect the C target to a high-power pulse power supply, set the micro-pulse parameters to 23 μs, the average power to 8 kW, the gas pressure to 2 Pa, the argon flow rate to 110 sccm, the bias voltage to -90 V, and the time to prepare the C coating for 40 min.
[0058] After the coating preparation is completed, the coating is allowed to stand for 40 minutes to obtain a Cr / CrN / WC / C nano coating.
[0059] The Cr / CrN / WC / C nano-coating prepared in this embodiment is as follows Figure 1 As shown, the left side of the figure is a coated boring tool, and the right side is an uncoated boring tool.
[0060] The Cr / CrN / WC / C nano-coating prepared in this example was subjected to an indentation test. The results are as follows: Figure 2 As shown in the figure, it can be seen that after the indentation test, no radiation cracks were generated, indicating that the fracture toughness is relatively high.
[0061] Example 2
[0062] The substrate was ultrasonically cleaned in ethanol for 20 min, and then taken out and dried with compressed air; the substrate was placed on the sample platform of the vacuum chamber and the vacuum degree was controlled to 1*10 -3 Pa; connect a pulsed DC power supply to the substrate, set the bias voltage to -300V, 90KHz, 3μs, the gas pressure to 2Pa, the argon flow rate to 110sccm, clean for 30min, and complete ion cleaning.
[0063] Connect the Cr target, enable high-power pulsed magnetron sputtering, set the micro-pulse parameters to 30μs, the average power to 4kW, the gas pressure to 2Pa, the argon flow rate to 110sccm, the bias voltage to -90V, and activate for 5min; then change the bias voltage to -80V to prepare a Cr metal bonding layer with a thickness of 400nm.
[0064] High-power pulsed magnetron sputtering was enabled, and the micro-pulse parameters were set to 10 μs, the average power to 6 kW, the gas pressure to 1.5 Pa, the argon flow rate to 100 sccm, the nitrogen flow rate to 40 sccm, and the bias voltage to -120 V to prepare a CrN nano-composite coating with a thickness of 300 nm.
[0065] The WC target was connected to a high-power pulse power supply, and the C target was connected to a pulsed DC power supply. The micropulse parameters of the pulsed magnetron sputtering of the WC target were 15 μs and the average power was 10 kW. The pulsed DC power supply parameters of the pulsed magnetron sputtering of the C target were 90 kHz, 5 kW, gas pressure 2 Pa, argon flow rate 110 sccm, nitrogen flow rate 120 sccm, and bias voltage -200 V to prepare a 700 nm WC nanocoating.
[0066] Connect the C target to a high-power pulse power supply, set the micro-pulse parameters to 20 μs, the average power to 6 kW, the gas pressure to 1 Pa, the argon flow rate to 120 sccm, the bias voltage to -140 V, and the time to 60 min to prepare the C coating.
[0067] After the coating preparation is completed, the coating is allowed to stand for 50 minutes to obtain a Cr / CrN / WC / C nano coating.
[0068] Example 3
[0069] The substrate was ultrasonically cleaned in acetone for 20 min, and then taken out and dried with compressed air; the substrate was placed on the sample platform of the vacuum chamber and the vacuum degree was controlled to 1*10 -3 Pa; connect a pulsed DC power supply to the substrate, set the bias voltage to -600V, 110KHz, 3μs, the gas pressure to 2Pa, the argon flow rate to 100sccm, clean for 40min, and complete ion cleaning.
[0070] Connect the Cr target, enable high-power pulsed magnetron sputtering, set the micropulse parameters to 10μs, the average power to 5kW, the gas pressure to 1.8Pa, the argon flow rate to 115sccm, the bias to -100V, and activate for 3min; then change the bias to -70V to prepare a Cr metal bonding layer with a thickness of 350nm.
[0071] High-power pulsed magnetron sputtering was enabled, and the micro-pulse parameters were set to 30 μs, the average power to 3 kW, the gas pressure to 1.5 Pa, the argon flow rate to 100 sccm, the nitrogen flow rate to 60 sccm, and the bias voltage to -110 V to prepare a CrN nano-composite coating with a thickness of 420 nm.
[0072] The WC target was connected to a high-power pulse power supply, and the C target was connected to a pulsed DC power supply. The micropulse parameters of the pulsed magnetron sputtering of the WC target were 17μs and the average power was 7kW. The pulsed DC power supply parameters of the pulsed magnetron sputtering of the C target were 95kHz, 6kW, gas pressure 2Pa, argon flow rate 120sccm, nitrogen flow rate 100sccm, and bias voltage -180V to prepare a 1200nm WC nanocoating.
[0073] Connect the C target to a high-power pulse power supply, set the micro-pulse parameters to 35 μs, the average power to 5 kW, the gas pressure to 1 Pa, the argon flow rate to 105 sccm, the bias voltage to -90 V, and the time to prepare the C coating for 45 min.
[0074] After the coating preparation is completed, the coating is allowed to stand for 40 minutes to obtain a Cr / CrN / WC / C nano coating.
[0075] Example 4
[0076] The substrate was ultrasonically cleaned in acetone for 15 min, and then taken out and dried with compressed air; the substrate was placed on the sample platform of the vacuum chamber and the vacuum degree was controlled to 0.6*10 -3 Pa; connect a pulsed DC power supply to the substrate, set the bias voltage to 300V, 95KHz, 3μs, the gas pressure to 1.8Pa, the argon flow rate to 110sccm, clean for 50min, and complete ion cleaning.
[0077] Connect the Cr target, enable high-power pulsed magnetron sputtering, set the micro-pulse parameters to 15μs, the average power to 8kW, the gas pressure to 2Pa, the argon flow rate to 105sccm, the bias voltage to -70V, and activate for 5min; then change the bias voltage to -60V to prepare a Cr metal bonding layer with a thickness of 260nm.
[0078] High-power pulsed magnetron sputtering was enabled, and the micro-pulse parameters were set to 25 μs, the average power to 7 kW, the gas pressure to 1.1 Pa, the argon flow rate to 120 sccm, the nitrogen flow rate to 40 sccm, and the bias voltage to -100 V to prepare a CrN nano-composite coating with a thickness of 340 nm.
[0079] The WC target was connected to a high-power pulse power supply, and the C target was connected to a pulsed DC power supply. The micropulse parameters of the pulsed magnetron sputtering using the WC target were 28μs and the average power was 9kW. The pulsed DC power supply parameters of the pulsed magnetron sputtering using the C target were 108kHz, 7kW, gas pressure 2Pa, argon flow rate 115sccm, nitrogen flow rate 120sccm, and bias voltage -90V to prepare a 720nm WC nanocoating.
[0080] Connect the C target to a high-power pulse power supply, set the micro-pulse parameters to 30 μs, the average power to 7 kW, the gas pressure to 1 Pa, the argon flow rate to 120 sccm, the bias voltage to -120 V, and the time to prepare the C coating for 50 min.
[0081] After the coating preparation is completed, the coating is allowed to stand for 60 minutes to obtain a Cr / CrN / WC / C nano coating.
[0082] The Cr / CrN / WC / C nano coatings prepared in Examples 1 to 4 were subjected to performance tests, and the results are recorded in Table 1.
[0083] Table 1 Performance test results
[0084] sample Binding force Hardness(GPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Elastic recovery (%) Example 1 ≥HF1 38.9 4.7 67.2 Example 2 ≥HF1 41.5 3.4 64.8 Example 3 ≥HF1 42.3 3.3 63.1 Example 4 ≥HF1 41.8 3.5 65.4
[0085] It can be seen from the above embodiments that the present invention provides a Cr / CrN / WC / C nano coating with excellent film-base bonding, elastic recovery, hardness and fracture toughness, which is suitable for small hole and deep hole boring tool cutting and significantly improves cutting performance and life.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Cr / CrN / WC / C nano coating, characterized in that: From bottom to top, they are Cr metal bonding layer, CrN nanocomposite coating, WC nanocoating and C coating; The thickness of the Cr metal bonding layer is 200-500nm; the thickness of the CrN nano-composite coating is 300-500nm; and the thickness of the WC nano-coating is 600-1500nm.
2. The method for preparing the Cr / CrN / WC / C nano coating according to claim 1, characterized in that: It includes the following steps: (1) Using Cr target material to activate and pulse magnetron sputter the substrate to form a Cr metal bonding layer; (2) using a Cr target to perform pulsed magnetron sputtering on the surface of the Cr metal bonding layer to form a CrN nanocomposite coating; (3) pulsed magnetron sputtering is performed on the surface of the CrN nanocomposite coating using a WC target and a C target to form a WC nanocoating; (4) Using a C target material to perform pulsed magnetron sputtering on the surface of the WC nano coating to form a C coating, thereby obtaining the Cr / CrN / WC / C nano coating.
3. The method for preparing the Cr / CrN / WC / C nano coating according to claim 2, characterized in that: The activation micro-pulse parameters in step (1) are 2 to 40 μs, average power is 2 to 10 kW, gas pressure is 0.3 to 2 Pa, argon gas flow rate is 100 to 130 sccm, and bias voltage is -30 to -200 V.
4. The method for preparing the Cr / CrN / WC / C nano coating according to claim 2 or 3, characterized in that: The bias voltage of the pulsed magnetron sputtering in step (1) is -60 to -100V.
5. The method for preparing the Cr / CrN / WC / C nano coating according to claim 4, characterized in that: The micro-pulse parameters of the pulse magnetron sputtering in step (2) are 2 to 40 μs, the average power is 2 to 10 kW, the gas pressure is 0.8 to 2 Pa, the argon flow rate is 100 to 130 sccm, the nitrogen flow rate is 30 to 120 sccm, and the bias voltage is -60 to -150 V.
6. The method for preparing the Cr / CrN / WC / C nano coating according to claim 2 or 5, characterized in that: In step (3), the micro-pulse parameters of the pulsed magnetron sputtering of the WC target are 6 to 30 μs, and the average power is 6 to 10 kW; The pulsed DC power supply parameters for pulsed magnetron sputtering of the C target material in step (3) are 80 to 120 kHz, and the average power is 0.4 to 8 kW.
7. The method for preparing the Cr / CrN / WC / C nano coating according to claim 6, characterized in that: The gas pressure of the pulse magnetron sputtering in step (3) is 0.6 to 2 Pa, the argon flow rate is 100 to 130 sccm, the nitrogen flow rate is 100 to 130 sccm, and the bias voltage is -60 to -300 V.
8. The method for preparing the Cr / CrN / WC / C nano coating according to claim 2 or 7, characterized in that: The micro-pulse parameters of the pulse magnetron sputtering in step (4) are 2 to 40 μs, the average power is 2 to 10 kW, the gas pressure is 0.8 to 2 Pa, the argon gas flow rate is 100 to 130 sccm, the bias voltage is -60 to -150 V, and the time is 30 to 60 min.
9. Use of the Cr / CrN / WC / C nano coating according to claim 1 in small hole boring tools.
Citation Information
Patent Citations
Functionally-graded diamond-like carbon film as well as preparation method and product of functionally-graded diamond-like carbon film
CN106244986A
Superhard and tough nano-composite coating, preparation method and use equipment
CN113774347A
TiSiCN nano-composite coating, as well as deposition device, preparation method and application of TiSiCN nano-composite coating
CN113832440A
Preparation method of nano coating for propeller surface
CN117305762A
Lining gradient diamond -like carbon film's mould
CN206089795U